Tinjauan Permasalahan Teodise Kitab Ayub dan Relevansinya terhadap Penderita HIV/AIDS - Djogo, Emanuel (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
Suffering is not by any means a new phenomenon for human beings. Human and suffering are of one reality in life throughout the world. In the light of religious views, the phenomenon of suffering inexplicitly affirms the position of God as central within human life. Job’s suffering in the Christian Scriptures was narrated to contradict directly the ancient laws of retribution in the Old Testament tradition. The Author of the Book of Job seems to insinuate that suffering is not so much an effect of sin as a mystery of God. God is not the cause of suffering. Job’s misfortune draws the attention of his friends who speak in line with the tradition that it is caused by his own sinfulness and to which God has rightly vindicated. Their discussions on sin and suffering did not reach an agreement, however, to the point that eventually God must conclude the debate. The issue of unresolved suffering could properly be related to the distressed victims of HIV/AIDS. This association is intended to recommend the appropriate disposition and approaches to individuals with HIV/AIDS and those who are considered ‘victims’ of the illness, since they have been infected indirectly.